Roll of reporters serving Parliament, 1865-1918 - Victoria. Parliament. Legislative Assembly (1918)
MS roll of reporters from the various newspapers etc. who served Parliament between 1865-1918.
Manuscript reference no. : NLA MS 2010.
Xerox copy.
Location of original not known.
Keywords: Victoria. -- Parliament. -- legislative Assembly -- Reporters and reporting; Victoria. -- Parliament. -- Legislative Assembly -- Records and correspondence